Cortical Auditory Disorders: A Case of Non-Verbal Disturbances Assessed with Event-Related Brain Potentials - Sönke Johannes; Michael E. Jöbges; Reinhard Dengler; Thomas F. Münte (Behavioural Neurology)
In the auditory modality, there has been a considerable debate about some aspects of cortical disorders, especially about auditory forms of agnosia. Agnosia refers to an impaired comprehension of sensory information in the absence of deficits in primary sensory processes. In the non-verbal domain, sound agnosia and amusia have been reported but are frequently accompanied by language deficits whereas pure deficits are rare. Absolute pitch and musicians’ musical abilities have been associated with left hemispheric functions. We report the case of a right handed sound engineer with the absolute pitch who developed sound agnosia and amusia in the absence of verbal deficits after a right perisylvian stroke. His disabilities were assessed with the Seashore Test of Musical Functions, the tests of Wertheim and Botez (Wertheim and Botez, Brain 84, 1961, 19–30) and by event-related potentials (ERP) recorded in a modified 'oddball paradigm’. Auditory ERP revealed a dissociation between the amplitudes of the P3a and P3b subcomponents with the P3b being reduced in amplitude while the P3a was undisturbed. This is interpreted as reflecting disturbances in target detection processes as indexed by the P3b. The findings that contradict some aspects of current knowledge about left/right hemispheric specialization in musical processing are discussed and related to the literature concerning cortical auditory disorders.